Marine Plastics: Innovative Solutions to Tackling Waste - Grimstad, Siv Marina Flø; Ottosen, Lisbeth Mølgaard; James, Neil A. (Springer Nature, 2023)
This open access book reflects aims of the Blue Circular Economy (BCE) project, which focused on small and medium-sized enterprises (SMEs) aiming to create value using circular economy concepts related to products and services within fishing gear recycling in the Northern Periphery and Arctic (NPA) area. Cluster establishment and operation were carried out in collaboration with academia, industry and government agencies following a triple-helix approach. Discarded fishing gear constitutes a large part of marine plastics. Preventing future discharge of fishing gear into the ocean is a vital step in combating plastic pollution. Circular economy is one of the tools in the European Green deal, targeting waste minimisation. Closing the loop for waste fishing nets by transferring them to a resource could be a solution for preventing discharge at sea: exploring this opportunity is at the core of this book.